DEVELOPMENT OF A WEB-BASED PLATFORM FOR AUTOMATING AN INVENTORY MANAGEMENT OF A SMALL AND MEDIUM ENTERPRISE (FUDMA JOURNAL OF SCIENCES, 2022)
Nowadays, it has been noticed that the majority of businesses manually record and maintain their inventory data in spreadsheets with little to no technological innovation. This has many drawbacks in our contemporary society because it has been demonstrated that successfully monitoring inventories is difficult. This manual method of record keeping was labor-intensive, expensive, and error-prone, and it was unable to guarantee that the inventory remained current due to oversight and internal shrinkage. This study investigates the problems with manual inventory management and creates computerised inventory management software to solve those issues. By creating a computerised inventory management system to help storekeepers make decisions about their stocks, it suggests solutions to the current problems by keeping the records, tracking employee salaries, and updating sales and transactions. To be user-friendly, to accommodate all user requirements, and to adapt to future changes, the system was divided into various modules. The key ideas of the analysis and design methodology for the suggested system were outlined, and they were contrasted with those already in use. They also described how the system was designed and put into use using the MySQL database. The implemented methodology is illustrated with a case study. It is suggested that the computerised system developed in this study replace the manual system of stock recording and processing to make life easier for people, increase effectiveness, efficiency, and improve service delivery. Adopting this software will also reduce unnecessary stress, keep the account current, and simplify their work
Keywords: Computerized; Inventory Management; Account; Small and Medium Enterprise